SAINS UNTUK ANAK: HAKIKAT PEMBELAJARAN SAINS UNTUK SEKOLAH DASAR - Lily Barlia (LPMPP Universitas Negeri Yogyakarta, 2008)
Up to now, science educators are still confronted with· studentswho areunmotivated to learn science. They are generally unwilling to learn science forconceptualunderstanding. They relyon less appropriate learning strategies such asdistorting scientific knowledge to fit their existing knowledge, mindlesslyanswering questions, copying answers from others, or not completing their work.They also spend time and effort focusing·on less important learning.outcomes, .suchas memorizing science vocabulary or factual.information, rather than achievingscientific understanding. On the other hand,it is believed that motivation is animportant factor in the process of student learning for· conceptual understanding.This isa· sufficient reason for science educators to consider the .importance ofscience teaching strategies to increase students' motivation in the process ofstudent learning. In addition, they need to develop, refine, and reform the processof teachingand learning science itself. There are at least· three strategies they canuse to increase students' motivation to learn science for conceptual understanding:1) using immediate students' environment as learning· sources; 2) selectinginstruction materials related to students' existing knowledge;3) relating instructionmaterials to students' daily life needs. Finally, science educators haveto be awareof the importance of affective aspects and students' motivation to learn. They haveto decidehow to conduct instruction that can help students learn in meaningfulways, including understanding of why, where,and what for students learn science